Thermomechanical failure modeling and investigation into lining optimization for a Ruhrstahl Heraeus snorkel. (April 2016) - Jin, Shengli; Gruber, Dietmar; Harmuth, Harald; Rössler, Roman
Abstract: Snorkels used in Ruhrstahl Heraeus (RH) degassers in the steel industry undergo severe thermomechanical loads due to normal cyclic operations including preheating, submerging, and idle time. A finite element model was developed to simulate the first operational process cycle experienced by a RH snorkel. The presented analysis investigates the thermomechanical failure mechanisms of the magnesia chromite bricks in the wear lining. The Drucker–Prager, Drucker–Prager creep and fictitious crack models were applied to model creep and failure. The wedge-splitting test using an inverse analysis method, and the modified shear and compressive creep tests were utilized to characterize the mechanical properties of the refractories at elevated temperatures. The results show that at the beginning of the submerging process, tensile failure occurs closest to the hot face of the lowest refractory section prior to shear failure or creep. Because of refractory creep, the hot face of the wear lining does not experience shear failure during submerging. Furthermore, shear failure and creep contribute to the process of joint opening at the hot face. The concept of using less brittle material for the wear lining and a relative stiff monolith indicated that the tensile failure occurring from the hot thermal shock can be mitigated. Highlights: Parameters defining the plasticity and creep models were experimentally determined. Failure caused by hot thermal shock occurs at the region close to the hot face. Shear failure and creep account for the joint opening at the hot face. Roadmap to lining optimization of the snorkel is provided.